The Effectiveness of Team's Game Tournament Seen From Communication and Problem Solveing Capabilities (Experimental Study of Class VIII students in SMP Negeri 1 Seyegan) - Nuryadi Nuryadi; Nanang Khuzaini (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2016)
Cooperative learning is the type of Team's Games Tournament (TGT) which is a learning model in which there are stages such as games which can make the students communicate mathematically, more creative, have a positive attitude towards mathematics, and appropriate in solving mathematical problems. But in fact, communication skills and problem solving that should be owned by the students as a result of the learning process of mathematics meet the minimum completeness criteria (KKM). This study aims to describe the effectiveness of Cooperative learning of TGT type at mathematics learning in terms of communication skills and problem solving in class VIII SMP N 1 Seyegan the school year 2016/2017.  This research is a quasi ekspreriment research with pre-posttest nonequivalent control group design. This study uses two groups: the experimental group and the control group. The population study includes all students of class VIII which consists of four classes. From the existing population, it is drawn randomly two classes, namely VIII A and VIII C as samples. Mathematics Learning in class VIII A (experimental group) uses TGT type Cooperative learning and mathematics learning in class VIII C (control group) uses direct instruction. The instrument of this study is testing the communication and problem solving capability. To test the effectiveness of the study, it is used the analysis of one sample t-test. Whereas the T2 test hotteling is foolowed by univariate t-test which is used to determine more effective model. The result of research indicates that: (1) Cooperative learning of TGT-type and direct instruction in mathematics is effective in terms of communication skills and problem-solving; and (2) Cooperative learning of TGT type is more effective than direct instruction type in term of communication skill in class VIII SMPN 1 Seyegan. Keywords: TGT, mathematical communication, problem solving